Crossing Experiences in Digital Epigraphy. From Practice to Discipline - Rossi, Irene,De Santis, Annamaria (De Gruyter, 2018)
This miscellaneous volume collects contributions on nineteen projects dealing with Digital Epigraphy – they are diversified in geographic and chronological context, for script and language, and for typology of digital output. The objective is to point out the methodological issues which are specific to the application of information technologies to epigraphy, with a focus on data modelling and text annotation, lexicography and interoperability.
Keywords: epigraphy; ancient languages; data modelling; interoperability; lexicography; grapheme analysis; palaeography; digital humanities; translation; writing systems; text encoding; scripts